Grim. Volume two, Devils & dust - Phillips, Stephanie, 1991- (BOOM! Studios, 2023)
In her continuing macabre journey as a grim reaper, Jessica Harrow is still trapped in Las Vegas with fellow reapers Eddie and Marcel, where they encounter a fabulous twist on mythical Greek figures, as well as someone with the authority to get them out of their phantasmal dilemma. Jess' means of moving between the world of the living and the realm of the dead has also gone amok. When everyone becomes marked for death but no one is dying, the consequences could be catastrophic! Will Jessica find a way to return to the Afterlife and take her rightful place atop the throne? Or will Adira solidify her control, now that she's finally in possession of Death's scythe?